Optimalisasi Multimedia untuk Meningkatkan Motivasi Belajar Siswa pada Pelajaran Aqidah - Tri Marfiyanto; Bahtiar Hariyadi (EDUCATIO : Journal of Education, 2017)
The purpose in research is how to use multimedia in improving the motivation of learning students on the subjects of Aqidah. The data collection techniques used in this study are by using observation methods, interview methods, and documentation methods. While analyzing the results of this research, used qualitative descriptive analysis consisting of three parts is data collection as well as data reduction, data presentation, conclusion or verification. Research results have helped teachers in efforts to increase the motivation of learners in learning. To achieve this, teachers make variations on learning methods, using active learning methods, and using multimedia in the learning process. This kind of teaching can train learners to be more active in learning, and to awaken their desires in learning. So that with the effort students can achieve learning outcomes more maximally.